Strategi Pengembangan Wirausaha Pemuda Dalam Mewujudkan Wirausahawan Mandiri Dan Implikasinya Terhadap Ketahanan Ekonomi Keluarga (Studi pada Koperasi Sumekar di Kampung Sanggrahan Pathuk Kecamatan Ngampilan Kota Yogyakarta, Provinsi Daerah Istimewa Yogyakarta) - Lusmino - Basia; John Suprihanto; Armaidy Armawi (Universitas Gadjah Mada, 2016)
ABSTRACTEfforts to developed the young entrepreneurs was part of the national policy of youth development. This study aimed to analyzed the development strategy of entrepreneurial youth in realizing the independent entrepreneur in Sanggrahan Village Pathuk District of Ngampilan Yogyakarta, then to analyzed aspects of the constraints that occured during the running of entrepreneurship, the latter to analyzed the economic resilience of family entrepreneurs, in Sanggrahan Village Pathuk District of Ngampilan Yogyakarta.The method used was merging the descriptive method of qualitative and quantitative methods deskrftif, using structured interviews, questionnaires and literature. Youth development strategy to measured efforts in realizing the independent entrepreneur used seven indicators, in addition to measuring the economic resilience of the families of the young entrepreneurs in Sanggrahan Village Pathuk District of Ngampilan Yogyakarta where two indicators, was used namely income entrepreneurs with minimum wage standards and the family needs of Yogyakarta.Results of this study showed from 7 indicators of entrepreneurial development strategy in realizing the independent entrepreneur there were three (3) indicators which had not been effectively implemented by the youth, namely leadership, marketing and business legality. These were caused by a lack of resources and capital owned in an effort to developed product marketing and business legality, Indicator development strategy in realizing the independent entrepreneur in the form of motivation and creativity had been done well by the youth, but in terms of competition and market changes still encountered obstacles in the form product pricing efforts that did not refer to the policies set prices government in the form of changes in market prices the increase in fuel prices and electricity tariffs that would be a hindrance youth in becoming independent entrepreneur. From the total number of 36 (thirty six), young entrepreneurs family economic security aspects of revenue was earned by 67 percent and from the aspect of needs was obtained by 66.7 percent. The percentage thus showed that the economic resilience of the families their of the young entrepreneurs in Sanggrahan Village could not considered poor because earn above UMK average to met their primary, secondary, and tertiary needs. It was clearly a portrait of that strategy for achieving self employment had little impact on the economic resilience of the family but it had implications for the business development of the youth because they had not fully implement the strategy in realizing the independent entrepreneur. ABSTRAKUpaya mewujudkan wirausahawan muda merupakan bagian dari kebijakan nasional pembangunan kepemudaan. Penelitian ini bertujuan untuk menganalisis strategi pengembangan wirausaha pemuda dalam mewujudkan wirausahawan mandiri di Kampung Sanggrahan Pathuk Kecamatan Ngampilan Yogyakarta, kemudian untuk menganalisis aspek kendala-kendala yang terjadi selama menjalankan wirausaha, yang terakhir untuk menganalisis ketahanan ekonomi keluarga para wirausaha, di Kampung Sanggrahan Pathuk Kecamatan Ngampilan Yogyakarta.Metode yang digunakan yakni metode penggabungan antara metode deskriptif kualitatif dan metode deskiptif kuantitatif, dengan menggunakan wawancara terstruktur, kuesioner, studi pustaka observasi dan dokumentasi. Untuk mengukur strategi pemuda mengembangkan usaha dalam mewujudkan wirausahawan mandiri digunakan 7 indikator, selain itu guna mengukur ketahanan ekonomi keluarga para wirausahawan muda di Kampung Sanggrahan Pathuk Kecamatan Ngampilan Yogyakarta digunakan 2 indikator yakni, 1) pendapatan para wirausaha dengan standar upah minimum Kota Yogyakarta, dan 2) kebutuhan-kebutuhan keluarga.Hasil penelitian ini menunjukkan dari 7 indikator strategi pengembangan wirausaha dalam mewujudkan wirausahawan mandiri terdapat 3 (tiga) indikator yang belum dilaksanakan secara efektif oleh para pemuda yaitu kepemimpinan, pemasaran dan legalitas usaha. Hal ini disebabkan oleh kurangnya sumberdaya serta modal yang dimiliki dalam usaha mengembangkan pemasaran produk serta legalitas usaha, indikator strategi pengembangan dalam mewujudkan wirausahawan mandiri berupa motivasi dan kreativitas telah mampu dilakukan baik oleh para pemuda, namun dari segi persaingan usaha dan perubahan pasar masih menemui hambatan berupa penetapan harga produk usaha yang mengacu pada kebijakan harga yang telah ditetapkan pemerintah berupa perubahan harga pasar kenaikan harga bahan bakar minyak dan tarif dasar listrik yang justru menjadi hambatan pemuda dalam mewujudkan wirausahawan mandiri. Dari total wirausahawan muda sejumlah 36 (tiga puluh enam) orang, ketahanan ekonomi keluarga dari aspek pendapatan didapatkan sebesar 67 persen dan dari aspek kebutuhan didapatkan sebesar 66,7 persen. Persentase demikian menunjukkan bahwa ketahanan ekonomi keluarga para pemuda wirausaha di Kampung Sanggrahan dikategorikan tidak miskin karena memperoleh pendapatan di atas UMK rata-rata dan mampu memenuhi kebutuhan primer, sekunder, tersier. Hal ini jelas mengambarkan bahwa strategi dalam mewujudkan wirausaha tidak terlalu berimplikasi terhadap ketahanan ekonomi keluarga namun justru berimplikasi terhadap pengembangan usaha para pemuda karena belum menerapkan strategi penuh dalam mewujudkan wirausahawan mandiri.